Effects of acute altered gravity during parabolic flight and/or vestibular loss on cell proliferation in the rat dentate gyrus. (27th July 2017) - Zheng, Yiwen; Gliddon, Catherine M.; Aitken, Phillip; Stiles, Lucy; Machado, Marie-Laure; Philoxene, Bruno; Denise, Pierre; Smith, Paul F.; Besnard, Stephane
Highlights: The effects of altered gravity on the hippocampus are poorly understood. We investigated the effects of parabolic flight on cell proliferation in the dentate gyrus (DG). We quantified the number of BrdU-labelled cells in the DG of rats undergoing parabolic flight. Some had an intact vestibular system and others bilateral vestibular deafferentation (BVD). BVD caused a large and significant reduction in the number of BrdU-positive cells irrespective of parabolic flight. Abstract: Both parabolic flight, i.e. a condition of altered gravity, and loss of vestibular function, have been suggested to affect spatial learning and memory, which is known to be influenced by neurogenesis in the hippocampus. In this study we investigated whether short alternated micro- and hyper-gravity stimulations during parabolic flight and/or loss of vestibular function, would alter cell proliferation in the hippocampal dentate gyrus of rats, by measuring the number of bromodeoxyuridine (BrdU)-incorporated cells. Rats were randomly allocated to the following experimental groups: (1) sham transtympanic saline injection only (n = 5); (2) bilateral vestibular deafferentation (BVD) by sodium arsanilate transtympanic injection only (n = 5); (3) sham treatment and parabolic flight (n = 5); (4) BVD and parabolic flight (n = 6). Forty-two days following transtympanic injection, the animals were subjected to parabolic flight in an awake restrained condition after habituation. A modified Airbus A300 aircraft was flown on a parabolic path, creating 20 s of 1.8 G during both climbing and descending and 22 s of 0 G at the apex of each parabola. The no flight animals were subjected to the same housing for the same duration. Immediately after the parabolic flight or control ground condition, animals were injected with BrdU (300 mg/kg, i.p). Twenty-four hs after BrdU injection, rats were sacrificed. BrdU immunolabelling was performed and the number of BrdU +ve cells in the dentate gyrus of the hippocampus was quantified using a modified fractionator method. BVD caused a large and significant reduction in the number of BrdU-positive cells compared to sham animals (P ≤ 0.0001); however, flight and all interactions were non-significant. These results indicate that BVD significantly decreased cell proliferation irrespective of the short exposure to altered/modified gravity.